Overskilling and human capital underutilisation in contemporary labour markets: A conceptual review - Nik Hassan, Nik Suriati; Ab Rani, Nor Zuriati Amani; Mohd Hassan, Norsilawati; Zahari, Nor Sabrina; Zulqernain, Nurul Syaqirah (Journal of Islamic, Social, Economics and Development, 2026)
Overskilling, defined as the inadequate use of a worker's skills relative to job requirements, is becoming more common in today's labour markets. This pattern raises substantial issues about the efficacy of investments in education and training. The paper examines existing research and policies to help people better understand overskilling and its connections to related concepts. It combines ideas from interpretive labour economics and offers a conceptual framework that connects the causes, processes, and effects of overskilling. Despite continuous investments in education and skill development, numerous economies encounter challenges, such as graduate underemployment and skill mismatches, resulting in the inefficient utilisation of human capital. The review provides the definition of overskilling, examines its underlying causes and effects, and underscores gaps in the current knowledge. Through the development of a framework, the study demonstrates the interconnection between the expansion of education, labour market changes, and the underutilisation of human capital. Moreover, it analyses the broader implications of overskilling for sustainable economic growth, underscoring the necessity for policymakers, especially in emerging and developing countries, to enhance skill utilisation. The study provides a thorough overview of various observations concerning overskilling and lays the groundwork for future empirical research and policy initiatives aimed at addressing this significant issue.